Karyological studies of eight Carduus L. (Asteraceae, Cardueae) taxa from Turkey - Gedik, Osman; Kiran, Yasar; Arabaci, Turan; Kostekci, Serkan (Firenze Univ Press, 2016)
The somatic chromosome numbers and detailed morphometric properties of 18 specimens belonging to eight taxa (six species) of genus Carduus L. distributed in Turkey were examined. The somatic chromosome numbers were determined as 2n = 2x = 22 in C. olympicus Boiss. subsp. hypoleucus (Bornm.) P. H. Davis, C. tmoleus Boiss. subsp. tmoleus and C. acanthoides L. s.l.; 2n = 2x = 18 in C. candicans Waldst. & Kit. s.l. and 2n = 2x = 16 in C. nutans L. subsp. falcato-incurvus P. H. Davis (2798). In addition, tetraploid chromosome numbers (2n = 4x = 32) were also observed in C. nutans subsp. falcato-incurvus (2737) and C. onopordioides Fisch. ex M. Bieb. subsp. turcicus (Kazmi) P. H. Davis. Karyotype analysis indicated that chromosomes of Carduus taxa generally have median region (m) and submedian region (sm) karyotypes. A median point (M) karyotypes is found in C. acanthoides subsp. acanthoides (2728). Secondary structures and one to three pairs of satellite chromosomes (sat-chromosome) were observed in some of the examined specimens. The findings for each of the analysed taxa are compared with the results of previous studies. The chromosome number and morphology of C. olympicus subsp. hypoleucus, C. nutans subsp. falcato-incurvus, C. onopordioides subsp. turcicus, C. candicans subsp. globifer and C. acanthoides subsp. sintenisii are reported here for the first time.
Keywords: Compositae; chromosome number; ideogram; new count; Turkey